Determination of the optimal horizontal boring mill for the repair of the pipe-rolling reduction-stretching mill’s body stands - O. N. Filonchik (Литьë и металлургия)
The article defines the optimal equipment necessary for the repair of the body stands of a pipe-rolling reduction-stretching mill. The body stand of the mill crate, made of 40X structural alloy steel, undergoes wear of the bearing seats during operation. Body stands restoration is carried out by surfacing the worn surfaces of the part with subsequent machining to the dimensions specified in the design documentation. In the process of surfacing medium-carbon steels, carbides are formed, which leads to a sharp increase in hardness in the zone of thermal influence, which affects the durability of carbide plates and processing accuracy.It is necessary to consider the geometric shape, dimensions, weight and material of the part while choosing equipment for repairing the body stand. Using a horizontal boring machine with a horizontal spindle performing rotational and translational movement of the axial feed, it is necessary to take into account the rigidity of the spindle, which affects the accuracy of processing, especially when restoring deep holes after surfacing with hardening surfacing materials. Bending the spindle can cause vibration and beating, which will affect the quality of the work performed. An increase in the rigidity of the machining can be achieved by using a drilling rod or by increasing the diameter of the spindle. Since it is necessary to restore deep blind holes in the repaired housing, it is impossible to use a drilling rod. In the process of work, the optimal diameter of the spindle of the horizontal boring machine was determined, taking into account the design features of the work piece.